Menurunkan Stres Akademik melalui Intervensi Psikoterapi Berbasis Mindfulness pada Mahasiswa Generasi Z - Zuyina Luklukaningsih; Dwi Wahyuni Uningowati (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aimed to determine the effectiveness of a Mindfulness -based psychotherapy intervention in reducing academic stress levels experienced by college students. The study used a pretest–posttest design without a control group, involving 10 active college students purposively selected based on moderate to high levels of academic stress. The intervention was implemented over two days and included reflective exercises and guided experiences focused on the application of the seven Mindfulness principles according to Kabat-Zinn (2015): non-judgment using personal standards, patience, a beginner's mind, trust, effortlessness, acceptance, and letting go. Data were collected using an academic stress scale that measures four aspects: coursework pressure, demands for satisfactory grades, time management for studying, and social support. Data were analyzed quantitatively using a paired-samples t-test. The results showed a significant decrease in academic stress levels from an average score of 73.1 to 58.5, indicating that this intervention was effective in helping students manage academic stress more consciously, calmly, and adaptively. This condition suggests that psychotherapy intervention through Mindfulness training can be a strategy to support students' psychological well-being in academic environments. Keywords: Mindfulness , academic stress, psychotrophic intervention, students